Perumusan Konsep Dasar dan Tema Rancangan Pada Perencanaan dan Perancangan Agrowisata Kopi di Kecamatan Kintamani: Bahasa Indonesia - I Gede Agus Ryananta Mudawan; I Wayan Widanan; Ni Wayan Meidayanti Mustika (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Coffee is one of the main plantation commodities in Indonesia which is one of the plantations that boosts the country's economy. Bali is one of the provinces that has quite extensive coffee plantations with an annual income of up to 15.5 thousand tons. Coffee Agrotourism is an educational tourism activity that utilizes coffee plantations as a tourist attraction. The utilization of this business in the plantation sector includes processing coffee from the plantations of local residents so that it becomes a product with national and even international selling value, in other words the products produced can not only be enjoyed by the domestic community, but also can be enjoyed by the outside community. Not only processed products are presented, but also experience, understanding, and knowledge about coffee or coffee plantations is also presented as a means of education. Coffee agrotourism is developed by utilizing the potential of both natural resources and human resources. Keywords: Coffee, Plantation, Education, Recreation, Agrotourism